PELATIHAN PEMBUATAN DETERJEN CAIR UNTUK PAKAIAN BAGI WARGA WONOSALAM, NGAGLIK, YOGYAKARTA - Purwanti, Ani; Kurniawati, Mukasi Wahyu; Sulistyaningsih, Eka; Khasanah, Rahayu (LPPM IST AKPRIND Yogyakarta, 2024)
Detergent is a cleaning material widely used in households. It comes in liquid, cream, and powder forms. Despite having the same function, they differ in their forms. Previously, liquid soap was only used for cleaning kitchen utensils, but now it is also used for laundry purposes because it is practical and removes oil stains effectively. The examination turns out that making liquid detergent is easy and people can make this themselves at a low cost. In order to expand the knowledge of PKK Mother’s Association in RT05 RW09, Wonosalam, Sukoharjo, Ngaglik, Sleman, Yogyakarta, the head of the RT05 proposed the Head of LPPM to grant permission for instructors from the Department of Chemical Engineering and Environmental Engineering at IST AKPRIND to provide training on making liquid detergent for laundry on Sunday, October 9, 2022. The community service activity conducted to provide knowledge on how to economically produce liquid detergent compared to products sold in the market, and ensure that this knowledge can serve as a foundation for entrepreneurship. The activity is carried out through the stages of licensing, training, and mentoring that provide information on economical side of liquid detergent, the materials that can be used, and the steps of production. Participants in this community service activity practicing making liquid detergent under the guidance of expert from IST AKPRIND. The training process runs smoothly, with many mom enthusiastically participating.